2018
DOI: 10.15517/rbt.v66i1.33267
|View full text |Cite
|
Sign up to set email alerts
|

Zooplankton variation in Fraijanes Lake (Costa Rica) during the course of one year

Abstract: Zooplankton in small tropical lakes has been little studied and its variation during the year may respond to different factors. In this study, the zooplankton of a small neotropical lake was studied at different times during one year and compared with changes in the lake conditions and in phytoplankton composition. The lake stratifies from March until September, and mixes during the hemispherical winter, from October until February. Besides the lake show a seasonal fluctuation in water level according to the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
1
1
0
4
Order By: Relevance
“…González et al (2004) found that in their case, an increase in water level at the reservoir during the rainy season, produced a decline in phytoplankton abundance and productivity, as a result of the dilution of the nutrient concentration. A similar pattern was observed in Lake Fraijanes (Umaña-Villalobos, Avilés-Vargas, & Esquivel-Garrote, 2018).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…González et al (2004) found that in their case, an increase in water level at the reservoir during the rainy season, produced a decline in phytoplankton abundance and productivity, as a result of the dilution of the nutrient concentration. A similar pattern was observed in Lake Fraijanes (Umaña-Villalobos, Avilés-Vargas, & Esquivel-Garrote, 2018).…”
Section: Discussionsupporting
confidence: 84%
“…In Costa Rica there are a few studies focused on zooplankton variations. For example, in Fraijanes Lake there is a study about zooplankton variations for one year (Umaña-Villalobos, Avilés-Vargas, & Esquivel-Garrote, 2018) and in Barva Lake there is a study about the phytoplankton variations for one year (Umaña-Villalobos, 2010).…”
mentioning
confidence: 99%
“…Основной вклад в видовое богатство обследованных озер вносили коловратки, что характерно и для других зарастающих водоемов [14,15,33,34,35,36,37]. Такие виды как B. hudsoni, B. angularis, A. rectangula, Сh.…”
Section: материалы и методыunclassified
“…Актуальность исследования малых водоемов для понимания их роли в сохранении биологического разнообразия [3] была признана сравнительно недавно [3,13]. Очевидно, именно по этой причине сравнительно немного публикаций, посвященных исследованию гидрофауны этой категории водоемов [14,15,16]. Также как и в других регионах, в Казахстане гидробиологические исследования охватывают преимущественно важные в хозяйственном отношении водные объекты -крупные озера, реки, водохранилища [17,18,19,20,21].…”
Section: Introductionunclassified
“…Актуальность исследования малых водоемов для понимания их роли в сохранении биологического разнообразия [3] была признана сравнительно недавно [3,13]. Очевидно, именно по этой причине сравнительно немного публикаций, посвященных исследованию гидрофауны этой категории водоемов [14,15,16]. Также как и в других регионах, в Казахстане гидробиологические исследования охватывают преимущественно важные в хозяйственном отношении водные объекты -крупные озера, реки, водохранилища [17,18,19,20,21].…”
Section: Introductionunclassified